Systems, Automation, and Control - Derbel, Faouzi; Derbel, Nabil; Kanoun, Olfa (Advances in Systems, Signals and Devices ;, 2019)
The book presents selected, extended and peer reviewed papers from the International Multiconference on System, Automation and Control held Leipzig in 2018. These are complemented with solicited contributions by international experts. Main topics are automatic control, robotics, synthesis of automation systems. Application examples range from man-machine interaction, mechatronics, on to biological and economical models.